ANALISIS KUALITAS LAYANAN PUBLIK di DESA SIDOMULYO KECAMATAN KEBONAGUNG KABUPATEN PACITAN 2025 - Gusval Wibowo gusval; Muhammad Awal Satrio Nugroho (Jurnal Riset Manajemen Akuntansi Indonesia, 2026)
This study aims to analyze the quality of public services in Sidomulyo Village, Pacitan Regency, using the SERVQUAL approach which includes five key dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The research employs a qualitative descriptive method with data collected through interviews, observation, and documentation. The results show that public service quality in Sidomulyo Village is relatively good in terms of tangibles and assurance, yet still needs improvement in reliability, responsiveness, and empathy. The local government has taken several initiatives, such as digitalizing services through the SISAPI application, enhancing cross-sector coordination, and strengthening communication with citizens. These findings suggest that continuous capacity building for village officials and optimizing digital-based public services are crucial to achieve effective and responsive service delivery at the village level.